Brain Hemodynamics and Cerebrovascular Reactivity in Patients with Tension-Type Headache - Ya. Abdullaiev, Rizvan; I. Kalashnikov, Valeriy; L Tovazhnyanska, Olena; N. Stoyanov, Alexander; I. Kauk, Oksana (Journal of Neurological Research And Therapy, 2019)
Introduction: Tension-type headache (TTH) is very common, with a lifetime prevalence in the general population ranging in different studies between 30% and 78%. TTH, divided into episodic and chronic types, introduced in the manual "International Classification of Headache Disorders"(ICHD-I), is of practical importance. Infrequent episodic headaches (no more than once a month) may not require drug therapy, but, on the contrary, frequent forms may require expensive treatment. Objective: To study the state of cerebral hemodynamics and cerebrovascular reactivity in patients with Tension-type headache and evaluate the efficacy of treatment with Phenibite using Doppler ultrasound. Materials and Methods: A retrospective analysis of the results of ultrasound dopplerography of the anterior, middle and posterior cerebral arteries (ACA, MCA and PCA), Vertebral and Basal (VA, BA) arteries was performed in 188 patients with TTH. Among them are infrequent episodic TTH - 68 (36,2%) patients, frequent episodic TTH - 64 (34,0%) patients, chronic TTH - 56 (29,8%) patients. The age of the subjects was 18-45 years, among them 85 (45.2%) men and 103 (54.8%) women. The maximum systolic velocity (Vs), the end diastolic velocity (Vd), the resistance and pulsativity indexes (RI, PI) in all vessels were determined. Patients were given consent to participate in the study. Results: Infrequent episodic (IFE) TTH were recorded in 86.4% of cases, frequent episodic (FE) — in 88.9%, and chronic (Ch) TTH — in 81.6% of cases. Bilateral TTH was noted in 39.2%, frontal localization - in 35.6%, in the occipital region - in 25–7% of cases. The asymmetry of the maximum systolic blood flow velocity (Vs) in the paired arteries within 20-30% was considered a violation of cerebral hemodynamics, which was detected in 38.7% of patients. An increase in Vs was noted in all cerebral vessels, especially in patients with FE TTH and chronic Ch TTH compared with the control group. In patients with IFE TTH the average value of RcFMt was 1.24±0.03, in patients with FE TTH - 1.25±0.02, in patients with Ch TTH - 1.27±0.03. In patients with TTH, hyper-responsiveness to hypercapnic test was detected: RcCO2 was 1.43±0.05 in the group with FE TTH; 1.39±0.07 in the group of Ch TTH and 1.37±0.04 in the group of IFE TTH, which indicates a tendency for the tension of the vasodilator regulation mechanism even in clinically insignificant forms of TTH. In the study of reactivity to the O2-test, a hyporeactive response was observed in the groups with FE TTH and Ch TTH (0.38±0.04 and 0.35±0.05, respectively. The treatment with Phenibut carried out in a step-by-step manner - during the first week the drug was applied at a dose of 250 mg 2 times a day, over the next 6 weeks the dose increased to 500 mg 2 times a day, then the dose was reduced back to 250 mg 2 times a day. Among patients with FE TTH, the frequency of headache decreased from 5.7±2.3 to 3.6±2.1 days/month, and in patients with Ch TTH - from 22.8±1.7 to 17.7±1,3 days/month (P<0,05). Influence of the drug was manifested at the initially increased RcFMt and RcCO2. A decrease in initially elevated RcCO2 was noted in all (FE TTH, ChTTH, IFETTH) clinical groups. However, this decrease was not statistically significant. Conclusion: In patients with TTH, an increase in the Vs is more often recorded, their asymmetry in the middle cerebral artery. Hyperreactivity on CO2-load is typical for patients with chronic TTH, and reflects the mobilization of metabolic regulation of cerebral blood flow. Conducting FMt was the most informative method for detecting autoregulatory disorders mainly in patients with IFE TTH. FE TTH in patients is characterized by the presence of a hyperactive reaction to hypercapnic and orthostatic tests, probably due to mobilization of humoral-metabolic and neurogenic links of regulation. In the group of patients with chronic TTH prevails hyporeactivity for hyperventilation test, reflecting the depletion of vasoconstriction reserve. The use of Phenibut(Noophen® (JSC Olainfarm Latvia in the treatment of TTH is accompanied by a decrease in the frequency of pain, and of pericranial muscle tone, most pronounced in patients with FE TTH. It's effectiveness is evident in the normalization of the coefficients of cerebrovascular reactivity in a patients with chronic TTH. The minimal statistical significance was observed on the dynamics of blood flow only in the VA.
Keywords: Transcranial dopplerography (TCD); Doppler ultrasound; Phenibut (Noophen); Cerebral Hemodynamic; Tension–type Headache (TTH).